A Modeling of Solutions and Strategy for Student Entrepreneurship Development (Case: Student Entrepreneurship Program at Medan) - Barus, Enny Segarahati; Marpaung, Muslim (Universitas Muhammadiyah Surakarta, 2019)
Purpose: This study aims to find the model for Student Entrepreneurship Development (Case Study Students who follow PMW in Medan) Methodology: Using ANP Method, By doing in-depth interviews and questionnaires to 4 lecturer of entrepreneurship courses and 3 students taking the PMW from Polytechnic of Medan and UISUResults: this study found that the most important internal solution of the Model was a proactive entrepreneurial solution, followed by capital and performance solutions, W (rater agreement) 0.2653, meaning that the level of respondent agreement on the order of prioritization was low. The most important performance solutions are solutions to increase profits, followed by increasing sales turnover and doing business development. W 0.1582 (very low agreement). The most important proactive entrepreneurial solution is a solution to improve entrepreneurship based on findings, improve perception and improve entrepreneurship based on experience, W = 0.1429 (very low). The most important capital solution is a solution to increase financial capital assistance, increase your own capital. W = 51.02%, high enough. The most important external solution is the solution for developing entrepreneurial intentions, university, and government support, W 14.29%, very low. The most important university support solutions are solutions to improve guidance, increase training, increase collaboration and curriculum development, W 0.61%, very low. The most important solution for developing entrepreneurial intentions is to improve experience, improve lecturer qualifications. W 0.7551, high. The ultimate government solution is to improve the rules, improve the policies. W 0.5102, quite high. The most important strategies are strengthening proactive attitudes, strengthening mentoring, strengthening capital and government supervision, W 0.3387 (low agreement).Applications/Originality/Value: The use of this model is expected to help stakeholders in making priority solutions and strategies that are appropriate in managing entrepreneurship programs for students.